Current Issues Bulletin: The Future of Inclusive Programs in Higher Education in the UK for Students with Intellectual Disabilities: Theory, Praxis, and Paradigms - Sue Carpenter (International Journal of Disability and Social Justice, 2023)
Universities in the UK are currently inaccessible to students with intellectual disabilities, although alternative non-matriculating programs for these students are growing throughout the rest of the world. The UK is far behind in this international movement although leading in the field of inclusive research. Incorporating student voices, this article explores the many benefits of inclusion in universities for these students as well as consequently for an academic community as a whole. It discusses stumbling blocks toward this aim, including ableism, and lists a number of potential models of inclusion that universities could adopt. Finally, it describes the goals and mission of the advocacy group IHE (UK) and outlines steps that have been taken so far to rectify this situation.